Family ties: young breast cancer patients and their children (Swiss Medical Weekly, 2015)
BACKGROUND: This study assessed the interaction of “family ties” in a cohort of young breast cancer patients. METHODS: Based on the Basel Breast Cancer Database, we analysed an unselected, consecutive cohort of patients who were ≤40 years at breast cancer diagnosis (n = 100). RESULTS: Sixty patients had children at the time of diagnosis (mean number of children: 1.03). Only four patients had desired children after BC therapy. The average age of the children at breast cancer diagnosis of their mother was 7.7 years. The mean age of the children whose mothers died of breast cancer at the time of their mother’s death was 13.1 years; these children (n = 37) lived an average of 84.7 months with the illness of their mother. Parity status was not a significant factor for compliance/persistence to adjuvant chemotherapy (p = 1.00). Patients who had children were more likely to be compliant/persistent to endocrine therapy (p = 0.021). Out of these patients, 41.2% rejected or discontinued endocrine therapy with the explicit intention to get pregnant. CONCLUSIONS: Desire for children was an important factor in refusing endocrine therapy. This clearly highlights the enormous pressure that many young women face in this situation. About a third of the children whose mothers were diagnosed with breast cancer experienced the palliative situation and the death of their mother. Since many of these children are confronted with a cancerous disease of their mothers during half of their childhood, special attention should be paid to age-appropriate support of a child in all phases of the mother’s disease.